2016
DOI: 10.1007/s11764-016-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-provider communication about sexual concerns in cancer: a systematic review

Abstract: Purpose Cancer survivors’ needs around sexual concerns are often unmet. The primary objective of this systematic review was to examine the prevalence of and factors associated with patient-provider communication about sexual concerns in cancer. Methods Using PRISMA guidelines, we searched PubMed/MEDLINE, PsychInfo, and CINAHL databases for peer-reviewed quantitative research papers (2000–2015) in cancer samples. Search terms across three linked categories were used (sexuality; communication; cancer). The Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
101
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 74 publications
7
101
0
3
Order By: Relevance
“…Providers should look beyond age when identifying patients who would most benefit from a discussion about sexual health and consider both sexual activity and partner status. Things I can do to help maintain my sexuality and intimacy 12 (14) 17 (20) Written resources regarding sexuality and intimacy 3 (4) 10 (12) Community resources regarding sexuality and intimacy 2 (2) 4 (5) Other 6 (7) 2 (2) I have never discussed any topics surrounding sexuality or intimacy with my health care team 32 (39) N/A *Percentages do not total 100% because multiple answers were allowed and not all patients provided an answer; the denominator is total patients (83).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers should look beyond age when identifying patients who would most benefit from a discussion about sexual health and consider both sexual activity and partner status. Things I can do to help maintain my sexuality and intimacy 12 (14) 17 (20) Written resources regarding sexuality and intimacy 3 (4) 10 (12) Community resources regarding sexuality and intimacy 2 (2) 4 (5) Other 6 (7) 2 (2) I have never discussed any topics surrounding sexuality or intimacy with my health care team 32 (39) N/A *Percentages do not total 100% because multiple answers were allowed and not all patients provided an answer; the denominator is total patients (83).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Additional factors include patient reluctance to ask for help when it is desired, feeling that it is the provider's responsibility to initiate sexual health discussions, and deferral to the provider to choose the topics that are important. 13,14 There is a critical need to better understand the experiences, needs, and preferences of women with gynecologic cancers regarding sexuality and sexual health care. In this study, the current provision of sexual health care is examined, along with patient factors that may be influencing provider decisions to discuss sexuality.…”
mentioning
confidence: 99%
“…37–43 Yet despite these calls to action, the majority of women experiencing treatment-related sexual dysfunction suffer without help. 44 Although oncology clinicians generally acknowledge the importance of addressing sexual health for women who have been treated for cancer 45,46 and patients say they want their physicians to ask about these concerns, 47,48 communication about sexual health is not part of routine care for most cancer patients and survivors. 44,49 Results of a recent systematic review published in Journal of Cancer Survivorship demonstrate that across different studies and a range of cancer sites, fewer than one third of women with cancer reported receiving information about potential sexual side effects of treatments, compared to twice as many men with cancer who had reported receiving such information.…”
mentioning
confidence: 99%
“…44,49 Results of a recent systematic review published in Journal of Cancer Survivorship demonstrate that across different studies and a range of cancer sites, fewer than one third of women with cancer reported receiving information about potential sexual side effects of treatments, compared to twice as many men with cancer who had reported receiving such information. 44 …”
mentioning
confidence: 99%
See 1 more Smart Citation